Technology, Long Work Hours, and Stress Worsen Work-life Balance in the Construction Industry - Holden, Simon; Sunindijo, Riza Yosia (International Journal of Integrated Engineering, 2018)
The aim of this research is to assess the level of work-life balance and to determine factors that affect work-life balance in the Australian construction industry. Questionnaires were used to collect data from 89 employees of a medium-sized construction organisation in Sydney, Australia. The results show that poor boundary management is responsible for the relatively low work-life balance. Technology, business culture, commute time, salary compensation, health, and the implementation of work-life balance initiatives are factors that influence work-life balance. On one hand, technology, long work hours, and stress can have negative impacts on work-life balance. On the other hand, work-life balance initiatives supported by appropriate business culture can promote better work-life balance in the construction industry. Construction organisations should make sure that work-life balance initiatives are made known to all employees and supported by top-level managers and those at the project level, so that employees are comfortable in using them. The initiatives should also cater the diverse needs of employees.